KEPAILITAN TERHADAP PERSEROAN TERBATAS YANG BERSTATUS SEDANG DALAM LIKUIDASI - Hadi Subhan (Perspektif, 2007)
The Company’s dissolution shall not cause the Company to lose its status as legal entity until the completion of liquidation and the report of the liquidator is accepted by the RUPS or by the court. For that, The company in liquidation shall be declared bankrupt through a Court decision. The outcome of bankruptcy of the company in liquidation to accelerate of liquidation of bankruptcy estate.